1995
DOI: 10.1111/j.1748-1716.1995.tb09872.x
|View full text |Cite
|
Sign up to set email alerts
|

Both gravity and non‐gravity dependent factors determine regional blood flow within the goat lung

Abstract: Distribution of pulmonary blood flow has traditionally been regarded as determined by gravity. This view has been challenged recently by reports describing marked gravity-independent distribution of flow. These reports were based on experiments in which local blood flow was measured by methods that have not been thoroughly evaluated. In the present study, we showed that in the goat lung regional trapping of i.v. infused microspheres (O = 15 microns) correlated to endothelial uptake of a simultaneously i.v. inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 27 publications
9
53
1
2
Order By: Relevance
“…The size of these particles (10 -150 m) causes them to become trapped in the pulmonary microcirculation in proportion to regional blood flow, which has been confirmed with other measurement methods (52). A maximum dose of MAA corresponds to ϳ700,000 particles, which occludes Ͻ1 ϫ 10 Ϫ4 % of the pulmonary capillaries (Mallinckrodt Medical, Petten, The Netherlands); according to one manufacturer the particles have a biological half-life of 11 h (Mallinckrodt Medical).…”
Section: Radiotracers For Imaging Of Regional Blood Flowsupporting
confidence: 59%
“…The size of these particles (10 -150 m) causes them to become trapped in the pulmonary microcirculation in proportion to regional blood flow, which has been confirmed with other measurement methods (52). A maximum dose of MAA corresponds to ϳ700,000 particles, which occludes Ͻ1 ϫ 10 Ϫ4 % of the pulmonary capillaries (Mallinckrodt Medical, Petten, The Netherlands); according to one manufacturer the particles have a biological half-life of 11 h (Mallinckrodt Medical).…”
Section: Radiotracers For Imaging Of Regional Blood Flowsupporting
confidence: 59%
“…Additionally, if the body position changes appreciably, this gradient reorients in the appropriate direction relative to the forces of gravity (Chaliki et al, 2002;Romand et al, 1994;Takeda et al, 1987). However, it is important to note that in quadrupeds such as horses (Hlastala et al, 1996), goats (Melsom et al, 1995), dogs (Parker et al, 1995), sheep (Walther et al, 1997), pigs , and ponies (Jarvis et al, 1992), gravity may not be as important a determinant of pulmonary blood flow distribution because the posture of quadrupeds produces a relatively shorter vertical gradient compared with those of humans (Hughes, 1996). In contrast, baboons, like humans, spend most of their time in the upright posture and have remarkably similar pulmonary structures and physiology to humans, where gravity plays a significant role in pulmonary blood flow (Glenny et al, 1999).…”
Section: Effects Of Gravity On Pulmonary Circulationmentioning
confidence: 94%
“…It has been shown that the number of trapped microsopheres in a piece of lung correlates closely to the pulmonary flow through that piece [9], and that the recovery of infused fluorescent-labelled microspheres is similar to that of radioactively labelled ones [ 101.…”
Section: Blood Flow Tracersmentioning
confidence: 99%